Problems of economic insolvency Kazakh enterprises - Bimendeyev, Zh. A. (Journal of Economic Research & Business Administration, 2015)
This article explores the practice and problems of insolvency Kazakh enterprises. Bankruptcy Institute is rated as the most important component of the national economy . According to the level of its development and effective regulation by the state is judged on the overall state of the economy and culture of entrepreneurship. The problem of insolvency organizations, businesses, business entities is a consequence of inefficient state legislative regulation, low culture andethics of the business sector , the problem of training the crisis managers, companies unwillingness to work in a tough competitive environment within the country or abroad , as well as the improvement of methods and not mechanisms to prevent the bankruptcy of all subjects of the national economy. Mechanisms for the prevention or control of insolvency and bankruptcy of enterprises should be very flexible to changes in the internal and external environment. Without solving these problems, we may face a more complex socio-economic consequences of the crisis in all its forms in our country.